2009
DOI: 10.1623/hysj.54.4.739
|View full text |Cite
|
Sign up to set email alerts
|

Groundwater recharge and flow in a small mountain catchment in northern Ethiopia

Abstract: The hydrodynamic behaviour of a sloped phreatic aquifer in the Tigray Highlands in northern Ethiopia is described. The aquifer is situated in the soils of a plateau on top of a basalt sequence and lies on steep slopes; the latter lead to hydraulic gradients that can cause high discharge fluxes. Distinct wet and dry seasons characterize the climate of the Tigray Highlands and recharge is absent during the dry season. Because of the fertile vertisols that have developed, the plateau is heavily cultivated and thu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
27
0

Year Published

2009
2009
2020
2020

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 45 publications
(27 citation statements)
references
References 16 publications
0
27
0
Order By: Relevance
“…Although an improved understanding of this relationship is strongly constrained by limited observational data sets (Carter & Parker, 2009;Howard & Griffith, 2009;MacDonald et al, 2009), a nascent but developing knowledge of the interactions between climate and groundwater is emerging and exemplified by contributions to this Special Issue (Mahé, 2009;Mileham et al, 2009;Nyenje & Batelaan, 2009;Olago et al, 2009;Walraevens et al, 2009;).…”
Section: Hydroclimatological Variability In Africamentioning
confidence: 99%
“…Although an improved understanding of this relationship is strongly constrained by limited observational data sets (Carter & Parker, 2009;Howard & Griffith, 2009;MacDonald et al, 2009), a nascent but developing knowledge of the interactions between climate and groundwater is emerging and exemplified by contributions to this Special Issue (Mahé, 2009;Mileham et al, 2009;Nyenje & Batelaan, 2009;Olago et al, 2009;Walraevens et al, 2009;).…”
Section: Hydroclimatological Variability In Africamentioning
confidence: 99%
“…Yet, the exact mechanisms and sediment sources are being scrutinized more recently in the Amhara sub-humid region (Bayabil et al, 2010;Setegn et al, 2010;Tebebu et al, 2010Tebebu et al, , 2015. Comparisons with the drier Tigray region (Nyssen et al, 2006;Vanmaercke et al, 2010;Walraevens et al, 2009;Zenebe et al, 2013) are helping to better understand and evaluate the performance of soil and water conservation measures. The quick generation and increased runoff and sediment in Shanko Bahir relative to the nearby sub-watershed were observable during field work and complicated previous modeling efforts .…”
Section: Discussionmentioning
confidence: 99%
“…In the semi-arid highlands of Ethiopia, studies have also shown the presence of saturation-excess as a mechanism, however, only during certain parts of the rainy season. In Tigray, infiltration-excess overland flow caused by heavy or high intensity storms has been shown to be common early in the rainy season (Descheemaeker et al, 2009;Walraevens et al, 2009;Zenebe et al, 2013). Thus, although these regimes occur with varying intensity in different watersheds, few attempts had been made to integrate both mechanisms in a satisfactory way.…”
Section: Contributing Runoff Mechanisms and Roads In The Subhumid Ethmentioning
confidence: 99%
“…The relationship between rainfall and recharge is not necessarily linear, with the possibility of recharge occurring sporadically on regional and temporal scales. In the Ethiopian highlands, for instance, recharge from monsoonal rains is released by spring and seeps in the dry season but this monsoonal recharge does not necessarily contribute to inter-annual groundwater storage (Walraevens et al, 2009). Contributing to the non-linearity of the relationship between rainfall and recharge, some studies suggest that a certain threshold of rainfall (annual or event-driven) must be reached before any recharge to groundwater occurs.…”
Section: Alterations To Surface Water and Groundwatermentioning
confidence: 99%
“…The decline of groundwater levels has been observed during periods of sustained annual reduction of rainfall such as during drought. Complete dewatering of certain aquifers was observed in Ethiopia during drought (Walraevens et al, 2009) and decline of groundwater levels observed during drought in Burkina Faso (Thiery et al, 1993) and in the upper Niger Basins (Bamba et al, 1996). It is suggested that the volume of groundwater extracted should not be greater than the volume recharged (Kinzelbach et al, 2003), and probably much less.…”
Section: Alterations To Surface Water and Groundwatermentioning
confidence: 99%